(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
Human capital was defined by Gary Becker (1975) as ‘any stock of knowledge or characteristics the worker has (either innate or acquired) that contributes to his or her productivity’. This knowledge was regarded as a form of capital because it was seen as enabling workers to invest in a set of marketable skills through gaining credentials that would enable them to increase their earnings. This commodification of human beings as a form of capital goods has been much criticised (e.g. Rubenson, 2015) but nevertheless has gained largely uncritical currency. It has been taken up by many international organisations, especially the Organisation for Economic Development (OECD) as a key driver of adult learning because ‘for individuals, investment in human capital provides an economic return, increasing both employment rates and earnings’ (OECD, 2001:3). When applied to literacy learning, this model of knowledge claims a universal relationship with economic development, individual prosperity and vocational achievement and this in turn leads to an assumption that skills-focused education is the most important. This perspective, which regards countries and their citizens as competitors in a global market place, then gets translated into measurable indicators such as those used in the Programme for the International Assessment of Adult Competencies (PIAAC) (OECD, 2016). These powerful standards become taken for granted in our everyday practices, meaning that the focus of education is on the national productivity agendas that are in the interests of industry rather than ordinary people (Rizvi and Lingard, 2010). In addition the narrow domains of skills-focused knowledge perpetuated by these interests become accepted as normal and so are difficult to challenge (Gorur, 2014).